Power in methods: language to infants in structured and naturalistic contexts. Issue 6 (16th January 2017) - Tamis‐LeMonda, Catherine S.; Kuchirko, Yana; Luo, Rufan; Escobar, Kelly; Bornstein, Marc H.
Abstract: Methods can powerfully affect conclusions about infant experiences and learning. Data from naturalistic observations may paint a very different picture of learning and development from those based on structured tasks, as illustrated in studies of infant walking, object permanence, intention understanding, and so forth. Using language as a model system, we compared the speech of 40 mothers to their 13‐month‐old infants during structured play and naturalistic home routines. The contrasting methods yielded unique portrayals of infant language experiences, while simultaneously underscoring cross‐situational correspondence at an individual level. Infants experienced substantially more total words and different words per minute during structured play than they did during naturalistic routines. Language input during structured play was consistently dense from minute to minute, whereas language during naturalistic routines showed striking fluctuations interspersed with silence. Despite these differences, infants' language experiences during structured play mirrored the peak language interactions infants experienced during naturalistic routines, and correlations between language inputs in the two conditions were strong. The implications of developmental methods for documenting the nature of experiences and individual differences are discussed. Abstract : Language inputs to infants were examined during 5 minutes of structured play and 45 minutes of naturalistic interaction at home. As seen in figures 3a to 3d, enormous intra‐individual fluctuations characterized the word tokens and types of infant‐directed speech during naturalistic interactions, whereas speech to infants during structured play was uniformly high and dense, with little fluctuation. Despite these differences, language input during structured play related strongly to language input during the peak 5 minutes of talk during naturalistic routines. Different methods yield different yet useful windows into the language experiences of infants.